End of Life: Kansans Deserve Excellent Care, Leaders Guide - Altus, Deborah (My University, 2000)
This publication for leaders is to help particiapnts understand that they have options for end-of life care.
MF2473_2000-10
Keywords: MF2473; Home and Family; Health and Safety; MF